Data, mining and innovation: qvo vadis, Europe? Analysis on the new exceptions for text and data mining - Jiménez Serranía, Vanessa (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Directive 2019/790 of the European Parliament and of the Council of 17 April 2019 on copyright and related rights in the digital single market has implemented certain exceptions on text and data mining. Although these exceptions might seem to provide a significant boost to this type of activities, their effects in practice are mitigated by the tightening of its wording, which is even likely to generate competitive distortions. This article aims to give a succinct and critical review of these new exceptions and to suggest some ways of improvement for the near future.